Adaptasi Masyarakat Adat Sungai Batu Terhadap Perubahan Iklim Di Desa Kubu Kabupaten Kotawaringin Barat - Djumaty, Brian L; Hayam Dey, Nina Putri (Metta : Jurnal Ilmu Multidisiplin, 2023)
Like other indigenous communities, the Sungai Batu Indigenous Community also experiences negative impacts due to climate change. This impact affects people's lives to survive. Based on this, this research aims to analyze the forms of adaptation that have been carried out by the Sungai Batu Indigenous community to climate change in Kubu Village, West Kotawaringin Regency. The research was conducted in June-December 2023 in Kubu Village, Kumai District, West Kotawaringin Regency. Using a descriptive qualitative approach. In determining research informants, the author used two techniques for determining informants, namely purposive sampling technique, and snowball sampling technique. The data collection techniques used were observation, interviews, documentation, and Focus Group Discussion (FGD). In data analysis, three techniques are used, namely data reduction, data presentation, and verification. Based on the results of the FGD in the field, it was found that in the adaptation, process there were many ways used by the Sungai Batu Indigenous community, but this was also not optimal in enabling the indigenous community to continue living. For this reason, further strategies are needed, such as increasing the human resources of indigenous communities, exploring their ecotourism potential, learning to make ecoprints, and diversifying agricultural product derivatives.